Hypercalcemia, Acute Kidney Injury, and Metabolic Alkalosis. (6th April 2022) - Aqeel, Faten; Del Castillo, Jennifer; Jaar, Bernard G.; Hanouneh, Mohamad
Abstract : Calcium regulation is tightly controlled in the body. Multiple causes of hypercalcemia have been studied including primary hyperparathyroidism, hypercalcemia of malignancy, and chronic granulomatous disorders. Among the less studied causes is calcium-alkali syndrome. Here, we discuss a case of hypercalcemia secondary to calcium-alkali syndrome, presenting with hypercalcemia, metabolic alkalosis, and acute kidney injury as a result of ingestion of a large amount of calcium supplements. Hypercalcemia can result in impaired collecting duct system sensitivity to antidiuretic hormone, afferent arteriole constriction, and activation of calcium sensor receptors in multiple tissues. The net effect is an increase in calcium reabsorption with a salt and water diuresis which leads to volume depletion, acute kidney injury, and metabolic alkalosis.